Simulation Modeling of Barrel Bore Wear under Dynamic Pressure Load - Zmindak, Milan; Pelagic, Zoran; Nagel, Martin; Smetanka, Lukas; Stankovicova, Zuzana (Communications - Scientific letters of the University of Zilina, 2015)
Wear is one of the major forms of material deterioration, often limiting both the life and the performance of the industrial components and requiring frequent replacement of the components. Wear is a very complex process and occurs by combination of several factors, such as the type of lubrication, loading speed, temperature materials, surface finishing and hardness. To simulate wear as a whole is very difficult, in many cases even not possible. The simulation by using the finite element method (FEM) is becoming increasingly popular and accessible. The FEM can also be used by solving mechanical wear, where it is critical to know the right way and method for arriving to the correct results. The method for obtaining additions of wear in the paper is developed on the base of previous practice, which used the combination of finite-element models and external algorithm for calculating wear. A FEM program ABAQUS has been used in this paper. The additions of degradation were obtained from an own developed script from MATLAB software, which is used to calculate selected equations and specific outputs in ABAQUS.